High-thermal-conductivity carbon skeleton resin-based composite material and preparation method thereof

By growing carbon nanotubes on mesophase asphalt-based carbon fibers and graphitized, a high-thermal carbon frame resin-based composite material is formed, which solves the problem of poor thermal conductivity of mesophase asphalt-based carbon fibers in polymers, and realizes the inter-fiber layer Improvement of thermal conductivity and the feasibility of large-scale industrial production.

CN119263865AActive Publication Date: 2025-01-07NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411532780.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-07
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

Mesophase bituminous carbon fibers have anisotropy, which leads to poor thermal conductivity between fiber layers when they are polymer thermal fillers. The existing processes are complex and costly, making it difficult to achieve large-scale industrial production.

Method used

By uniformly dispersing chopped mesophase asphalt-based carbon fibers in the dispersant solution, soaking in a mixed solution of the binder and the carbon nanotube growth catalyst, chemical vapor deposition is carried out to induce carbon nanotube growth, forming a porous hybrid network structure, and Graphitization treatment was carried out to prepare a highly thermally conductive carbon frame resin-based composite material.

Benefits of technology

A significant improvement in thermal conductivity between carbon fiber layers in polymers is achieved, reducing the contact thermal resistance of composite materials, forming a stable 3D high thermal conductivity network structure, improving the thermal conductivity between fiber layers, and suitable for thermal composite materials and heat. Manage materials field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263865A_ABST
    Figure CN119263865A_ABST
Patent Text Reader

Abstract

The invention discloses a high-thermal-conductivity carbon skeleton resin-based composite material and a preparation method thereof, and belongs to the technical field of thermal conductive composite materials. The preparation method comprises the following steps: firstly, preparing a fibrofelt preform from chopped mesophase pitch-based carbon fibers, and growing carbon nanotubes on the carbon fibers in situ by adopting a chemical vapor deposition process; depositing a layer of pyrolytic carbon through a chemical vapor infiltration process, and jointly connecting the carbon nanotubes / pyrolytic carbon with the chopped carbon fibers in the preform to prepare a porous hybrid network structure; carrying out graphitization treatment on the network structure to obtain a high-thermal-conductivity hybrid carbon skeleton composed of carbon fibers, carbon nanotubes and pyrolytic carbon; and impregnating polymer resin into the hybrid carbon skeleton structure through an impregnation process, and curing to obtain the carbon skeleton resin-based composite material. According to the prepared carbon skeleton resin-based composite material, when the volume fraction of the carbon skeleton accounts for 19.2 vol%, the thermal conductivity in the thickness direction of the composite material reaches 20.9 W / m.K which is 99 times of the thermal conductivity of pure epoxy resin, and the carbon skeleton resin-based composite material can be used as a novel thermal management material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermal conductive composite materials, and in particular relates to a high thermal conductive carbon skeleton resin-based composite material and a preparation method thereof. Background Art

[0002] Polymer materials have the characteristics of excellent processability and low density, and are widely used in various important industrial fields. However, the thermal conductivity of most polymer materials is very low. For example, the thermal conductivity of epoxy resin is 0.2 W / m·K, and the thermal conductivity of polydimethylsiloxane is 0.25 W / m·K, which restricts their application in the fields of thermal management and thermally conductive composite materials, such as heat dissipation devices for high-density integrated circuits, temperature control switches, green building materials and other applications. At present, there are two ways to improve the thermal conductivity of polymers: one is to improve the structure of the polymer itself, such as adjusting the polymer molecular chain structure to achieve an increase in thermal conductivity, but this method has limited effect on improving the thermal conductivity of polymers and is costly; the other is to introduce high thermal conductivity fillers into the polymer, including dispersed fillers and network structure fillers. Dispersed fillers are prone to agglomeration in the polymer, causing the actual thermal conductivity of the composite material to be far lower than the theoretical value. Network structure fillers are an effective method to improve the thermal conductivity of polymer materials. For example, thermal conductive fillers can be constructed into a 3D network structure through ice template method, chemical vapor deposition method, and sacrificial template method. This network structure can provide an effective high thermal conductivity transmission path and can achieve a significant improvement in the thermal conductivity of composite materials at a lower addition amount.

[0003] Ma et al. Chem. En. J. , 2020, 380: 122550” used the ice template method to prepare vertically arranged chopped carbon fibers and impregnated them with epoxy resin. When the carbon fiber filling amount was 13 vol%, the in-plane thermal conductivity of the composite material was 2.8 W / m·K; Uetani et al. Adv. Mater. , 2014, 26(33): 5857-5862. "After chopped carbon fibers were arranged vertically by electrostatic flocking and impregnated with resin, a thermal conductivity of 23.3 W / m·K was obtained when the carbon fiber addition amount was 13.2 wt%; Gonnet et al. Curr. Appl. Phys. , 2006, 6(1): 119-122." By filtering a carbon nanotube suspension under a magnetic field, a cross-linked network structure consisting of unidirectional nanotubes was prepared, and then impregnated with a low-viscosity epoxy resin. The in-plane thermal conductivity of the prepared composite material reached 42 W / m·K. The above method can effectively improve the thermal conductivity of the composite material by constructing a network structure through carbon fibers, but the process is complicated, the structure is difficult to control, and the cost and difficulty of large-scale industrial production are high.

[0004] Mesophase pitch-based carbon fiber is a carbon material with low density, high strength, high thermal conductivity, low thermal expansion coefficient and high modulus. It is an ideal filling material for improving the thermal conductivity of polymers and can be applied in the field of new thermal management materials. However, mesophase pitch-based carbon fiber has the following problems: it has obvious anisotropy, that is, the axial thermal conductivity is much greater than the radial thermal conductivity, resulting in poor thermal conductivity between fiber layers. Summary of the invention

[0005] The present invention is based on the inventors' discovery and understanding of the following facts and problems: mesophase asphalt-based carbon fibers have obvious anisotropy, and their axial thermal conductivity is much greater than their radial thermal conductivity, resulting in poor thermal conductivity between fiber layers. As a result, when used as a polymer thermal conductive filler, it has a poor effect on improving the thermal conductivity between carbon fiber layers in the polymer. In the prior art, the process of constructing a network structure by using mesophase asphalt-based carbon fibers is complicated, and the structure is difficult to control, resulting in high cost and difficulty in large-scale industrial production when used as a polymer thermal conductive material.

[0006] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present invention proposes a high thermal conductivity carbon skeleton resin-based composite material and a preparation method thereof, the preparation process is simple, the prepared high thermal conductivity carbon skeleton resin-based composite material has a three-dimensional porous hybrid carbon skeleton, a stable structure, and can achieve a significant improvement in the thermal conductivity of the resin-based carbon fiber composite material, especially improving the thermal conductivity along the interlayer direction of the carbon fiber in the polymer.

[0007] The present invention solves the above problems through the following solutions: The first object of the present invention is to provide a method for preparing a high thermal conductivity carbon skeleton resin-based composite material, comprising the following steps: The short-cut mesophase pitch-based carbon fibers are uniformly dispersed in a dispersant solution, vacuum-filtered, immersed in a mixed solution of a binder and a carbon nanotube growth catalyst, and dried to obtain a carbon fiber substrate material; After reducing the carbon fiber base material, inducing the growth of carbon nanotubes on the carbon fiber surface by chemical vapor deposition, and then depositing pyrolytic carbon by chemical vapor infiltration to obtain a porous hybrid network structure; graphitizing the porous hybrid network structure to obtain a porous hybrid carbon skeleton; The porous hybrid carbon skeleton is impregnated in a resin solution, and then solidified after the impregnation is completed, so as to obtain the high thermal conductivity carbon skeleton resin-based composite material.

[0008] The surface structure of the mesophase pitch-based carbon fiber itself is rough, and more catalysts can be fixed on its surface, so that the carbon nanotubes have more directions to grow; by controlling the chemical vapor deposition parameters, the degree to which the carbon nanotubes can extend freely becomes larger. The present invention grows radial carbon nanotubes on the surface of the mesophase pitch-based carbon fiber through chemical vapor deposition. The length of the carbon nanotubes reaches more than 100 μm, and can connect adjacent mesophase pitch-based carbon fibers to form a 3D thermal conductive network structure.

[0009] The present invention comprises three highly thermally conductive materials, namely, mesophase pitch-based carbon fiber, carbon nanotube and pyrolytic carbon, to form a 3D thermal conductive network structure. The pyrolytic carbon enhances the bonding strength of the overlap between the carbon fiber and the carbon nanotube, and the pyrolytic carbon is deposited along the carbon nanotube to increase the heat transfer path.

[0010] Since the surface activity of carbon fiber is low and the friction between fibers is large, the mesophase asphalt-based carbon fiber is easy to agglomerate in water, and the addition of a dispersant can improve the dispersibility of the carbon fiber in water. Therefore, preferably, the mass fraction of the dispersant used to disperse the chopped mesophase asphalt-based carbon fiber is 0.1-5 wt%, and the dispersant is one or more of sodium polyacrylate, polyvinyl pyrrolidone, and acrylic acid.

[0011] Preferably, the binder is one or more of polyvinyl alcohol, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, and polyethylene glycol; the carbon nanotube growth catalyst is one or more of ferrous sulfate, ferric nitrate, nickel nitrate, and cobalt nitrate; the mass fraction of the binder is 1 to 20 wt%, and the mass fraction of the carbon nanotube growth catalyst is 0.5 to 2 wt%. The impregnation process can be carried out under normal pressure or negative pressure. The main function of the binder is to bond the catalyst to the carbon fiber substrate and prevent the carbon fiber substrate structure from being destroyed during the soaking of the catalyst precursor. In order to avoid catalyst agglomeration caused by excessive binder concentration, the mass fraction of the binder is selected to be 1 to 20wt%.

[0012] Preferably, during chemical vapor deposition, an alkane precursor is introduced at 900-1100° C.; the alkane precursor is one or more of natural gas, methane, ethane, and propylene, and the flow rate of the alkane precursor is 0.05-0.5 L / min.

[0013] Generally, high temperature is more conducive to the formation of carbon nanotubes. The higher the temperature, the greater the catalyst activity. The metal catalyst with high reactivity grows faster under sufficient heat energy, and the longer the carbon nanotubes grow. However, high growth temperature will form catalyst agglomeration, affect the growth morphology of carbon nanotubes, and even destroy their tubular morphology to form carbon nanospheres. In the embodiment of the present invention, the growth temperature of carbon nanotubes is determined to be 900~1100℃, especially around 1020℃, where carbon nanotubes have higher growth efficiency and effect.

[0014] Preferably, the chemical vapor deposition time is 2 to 4 hours.

[0015] Preferably, during chemical vapor infiltration, the temperature is raised to 800-1200° C. and a pyrolytic carbon precursor is introduced; the pyrolytic carbon precursor is one or more of natural gas, methane, ethane, propylene, and ethanol, and the flow rate of the pyrolytic carbon precursor is 0.1-3 L / min.

[0016] Preferably, the chemical vapor infiltration time is 1 to 6 h.

[0017] Preferably, argon or nitrogen is introduced as a protective gas during the temperature rise process of chemical vapor deposition and chemical vapor infiltration.

[0018] Preferably, during chemical vapor deposition, the protective gas flow rate is 0.2-5 L / min, during catalyst reduction, hydrogen is used as a reducing agent, the hydrogen flow rate is 100-500 mL / min, and during carbon nanotube growth, the protective gas flow rate is 0.5-5 L / min.

[0019] Preferably, during the chemical vapor infiltration process, the flow rate of the protective gas during the heating process is 0.1-5 L / min, and the flow rate of the argon gas during the pyrolytic carbon deposition process is 0.2-5 L / min.

[0020] More preferably, when the graphitization treatment is performed, the heat treatment is performed at 2300° C. or higher.

[0021] Preferably, the resin is one or more of polysiloxane, epoxy resin, phenolic resin, polyurethane, and polyimide.

[0022] The second aspect of the present invention is to provide a high thermal conductivity carbon skeleton resin-based composite material prepared according to the above preparation method, in which adjacent carbon fibers are connected by carbon nanotubes or pyrolytic carbon.

[0023] Preferably, the length of the chopped mesophase pitch-based carbon fibers is 0.5-10 mm; and the length of the carbon nanotubes grown in the radial direction of the fibers can reach millimeter level.

[0024] Preferably, in the porous hybrid network structure, the volume fraction of the chopped mesophase pitch-based carbon fibers is 4.0-10.0%, the volume fraction of the carbon nanotubes is 0.2-10.0%, and the volume fraction of the pyrolytic carbon is 1.0-20.0%.

[0025] Further preferably, the thermal conductivity of the high thermal conductivity carbon skeleton resin-based composite material in the thickness direction is 9.0-22.0 W / m·K or higher. The so-called thickness direction is the direction perpendicular to the axial direction of the mesophase pitch-based carbon fiber.

[0026] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts short-cut mesophase pitch-based carbon fiber to make a porous fiber preform, and grows radial carbon nanotubes in situ on the surface of the carbon fiber in the preform by chemical vapor deposition. The length of the carbon nanotubes reaches more than 100 μm, connecting adjacent carbon fibers to form a 3D thermal conductive network structure, and depositing pyrolytic carbon on the substrate by chemical vapor infiltration, thereby enhancing the bonding strength of the overlap between the carbon fiber and the carbon nanotube, and finally performing graphitization treatment to prepare a high thermal conductivity hybrid carbon skeleton. The deposition of pyrolytic carbon improves the bonding strength between the carbon nanotubes and the carbon fiber, and at the same time, the overlap between the carbon fibers is converted from physical contact to covalent bond connection, so that the carbon nanotubes and the carbon fiber, and the carbon fiber and the carbon fiber support each other, and constructs a carbon nanotube / pyrolytic carbon network structure in a direction perpendicular to the carbon fiber, thereby reducing the contact thermal resistance of the hybrid carbon skeleton, forming a stable 3D high thermal conductive network structure, and realizing the improvement of thermal conductivity in the direction between the fiber layers. In some embodiments of the present invention, when the volume fraction of the hybrid carbon skeleton is 19.2 vol%, the thermal conductivity of the composite material along the thickness direction after impregnation with epoxy resin reaches 20.9 W / m·K, which is about 99 times higher than that of pure epoxy resin material, thereby achieving a significant improvement in the thermal conductivity of the composite material at a low thermal conductive filler filling amount.

[0027] The present invention is applicable to different application scenarios or requirements. It can realize the preparation of large-sized carbon skeletons by using processes such as filtration, chemical vapor deposition, and chemical vapor infiltration, and has broad application prospects and practicality in the fields of thermal conductive composite materials and thermal management materials. The preparation method proposed in the present invention can grow carbon nanotubes / pyrolytic carbon structures with different aspect ratios on carbon fibers by controlling process parameters such as carbon nanotube growth time and pyrolytic carbon deposition time, and construct hybrid carbon skeletons with different microstructures, which broadens the application field of carbon fiber reinforced resin-based composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a process flow chart of preparing a hybrid carbon skeleton according to an embodiment of the present invention; Figure 2 Schematic diagram of a carbon nanotube / pyrolytic carbon network structure constructed in an embodiment of the present invention, wherein short-cut mesophase pitch-based carbon fibers 1, carbon nanotubes 2, and deposited pyrolytic carbon 3; Figure 3 4 is a microscopic morphology of the hybrid carbon skeleton prepared in Example 1 of the present invention, wherein 4 is a carbon fiber deposited with pyrolytic carbon, and 5 is a carbon nanotube deposited with pyrolytic carbon; Figure 4 is the thermal conductivity of the high thermal conductivity hybrid carbon skeleton / resin-based composite material prepared in this embodiment of the present invention. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0030] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings: The present invention provides a method for preparing a high thermal conductivity carbon skeleton / resin-based composite material. Figure 1 As shown, it is a process flow chart for preparing a high thermal conductivity carbon skeleton / resin-based composite material in this embodiment, which mainly includes filtration, chemical vapor deposition of carbon nanotubes, chemical vapor infiltration pyrolytic carbon, high temperature heat treatment, vacuum impregnation, curing and other processes. The specific steps are as follows: Step 1, chopping the mesophase pitch-based carbon fiber into short pieces of 0.5-10 mm, and pre-oxidizing them in a muffle furnace to remove the sizing agent attached to the surface; Step 2, placing the chopped fibers prepared in step 1 into a dispersant solution, and stirring to obtain a uniformly dispersed chopped fiber suspension; Step 3, pouring the chopped fiber suspension into a suction filtration device, performing vacuum filtration, and obtaining a chopped fiber mat preform; Step 4, soaking the chopped fiber mat prepared in step 3 in a solution containing a binder and a carbon nanotube growth catalyst, vacuum impregnating and then drying; Step 5, placing the sample prepared in step 4 into a chemical vapor deposition furnace, heating it to 500-700° C., introducing hydrogen, and introducing an alkane precursor at 900-1100° C. to grow carbon nanotubes; Step 6, placing the sample prepared in step 5 into a chemical vapor infiltration furnace, heating it to 800-1200° C., introducing a pyrolytic carbon precursor, depositing pyrolytic carbon, and preparing a porous hybrid network structure; Step 7, placing the porous hybrid network structure into a graphitization furnace and heat treating it at 2300° C. to 2500° C. to obtain a porous hybrid carbon skeleton; Step 8, immersing the hybrid carbon skeleton in a resin solution, and curing after the immersion is completed to obtain a high thermal conductivity carbon skeleton / resin-based composite material.

[0032] The present invention uses short-cut mesophase pitch-based carbon fibers to make a porous preform, in-situ grows carbon nanotubes and deposits pyrolytic carbon on the carbon fiber surface in the preform by chemical vapor deposition, and finally performs graphitization treatment to prepare a high thermal conductivity hybrid carbon skeleton.

[0033] Example 1 Step 1, chop the mesophase pitch-based carbon fiber into 3-5 mm, take 0.15-0.3 g, and pre-oxidize in a muffle furnace at 390° C. for 90 min to remove the surface sizing agent; Step 2, placing the chopped fibers prepared in step 1 into a 20wt% sodium polyacrylate solution, and stirring by magnetic force to obtain a uniformly dispersed chopped fiber suspension; Step 3, pouring the chopped fiber suspension into a suction filtration device, performing vacuum filtration, and obtaining a chopped fiber mat preform; Step 4, soaking the chopped fiber mat prepared in step 3 in a 0.01 mol / L ferrous sulfate-polyvinyl alcohol solution, vacuum impregnating, and drying at 70° C. for 6-12 hours; Step 5, placing the sample prepared in step 4 into a chemical vapor deposition furnace, heating to 500°C under argon protection, with an argon flow rate of 1 L / min during the heating process; turning off the argon, introducing hydrogen and keeping warm for 1 hour, with a hydrogen flow rate of 200-250 mL / min, then turning off the hydrogen; introducing argon and heating to 1020°C, introducing natural gas, with a natural gas flow rate of 0.3 L / min, and keeping warm for 4 hours; Step 6, placing the sample prepared in step 5 into a chemical vapor infiltration furnace, heating to 1070°C under argon protection at 2.4 L / min, introducing natural gas at 0.8 L / min, and keeping the temperature for 6 h to prepare a porous hybrid network structure; Step 7, placing the porous hybrid network structure into a graphitization furnace and heat treating it at 2450° C. to obtain a porous hybrid carbon skeleton; Step 8, immersing the graphitized porous hybrid carbon skeleton in an epoxy resin solution, with the mass ratio of resin to curing agent being 100:26.5, and vacuum impregnating for 30 min; Step 9: Place the sample from step 8 in an oven, heat to 150°C, and cure for 120 min.

[0034] In this embodiment, the volume fraction of carbon fiber in the hybrid carbon skeleton is 4.5%, the volume fraction of carbon nanotubes is 1.5%, the volume fraction of pyrolytic carbon is 13.2%, the volume fraction of epoxy resin is 74.2%, and the thermal conductivity along the thickness direction of the composite material is 20.9 W / m·K.

[0035] Embodiment 2: Step 1, chop the mesophase pitch-based carbon fiber into 3-5 mm, take 0.15-0.3 g, and pre-oxidize in a muffle furnace at 390° C. for 90 min to remove the surface sizing agent; Step 2, placing the chopped fibers prepared in step 1 into a 20wt% sodium polyacrylate solution, and stirring by magnetic force to obtain a uniformly dispersed chopped fiber suspension; Step 3, pouring the chopped fiber suspension into a suction filtration device, performing vacuum filtration, and obtaining a chopped fiber mat preform; Step 4, soaking the chopped fiber mat prepared in step 3 in a 0.01 mol / L ferrous sulfate-polyvinyl alcohol solution, vacuum impregnating, and drying at 70° C. for 6-12 hours; Step 5, placing the sample prepared in step 4 into a chemical vapor deposition furnace, heating to 500°C under argon protection, with an argon flow rate of 1 L / min during the heating process; turning off the argon, introducing hydrogen and keeping warm for 1 hour, with a hydrogen flow rate of 200-250 mL / min, and then turning off the hydrogen; introducing argon and heating to 1020°C, introducing natural gas, with a natural gas flow rate of 0.3 L / min, and keeping warm for 4 hours; Step 6, placing the sample prepared in step 5 into a chemical vapor infiltration furnace, heating to 1070°C under argon protection at 2.4 L / min, introducing natural gas at 0.8 L / min, and keeping the temperature for 6 h to prepare a porous hybrid network structure; Step 7, placing the porous hybrid network structure into a graphitization furnace and heat treating it at 2450° C. to obtain a porous hybrid carbon skeleton; Step 8, immersing the graphitized porous hybrid carbon skeleton in a polydimethylsiloxane solution with a mass ratio of resin to curing agent of 100:26.5, and vacuum impregnating for 30 min; Step 9: Place the sample from step 8 in an oven, heat to 150°C, and cure for 120 min.

[0036] In this embodiment, the volume fraction of carbon fiber in the hybrid carbon skeleton is 4.4%, the volume fraction of carbon nanotubes is 2.4%, the volume fraction of pyrolytic carbon is 10.4%, the volume fraction of polydimethylsiloxane is 73.6%, and the thermal conductivity along the thickness direction of the composite material is 18.8 W / m·K.

[0037] Example 3 Step 1, chop the mesophase pitch-based carbon fiber into 3-5 mm, take 0.15-0.3 g, and pre-oxidize in a muffle furnace at 390° C. for 90 min to remove the surface sizing agent; Step 2, placing the chopped fibers prepared in step 1 into a 20wt% sodium polyacrylate solution, and stirring by magnetic force to obtain a uniformly dispersed chopped fiber suspension; Step 3, pouring the chopped fiber suspension into a suction filtration device, performing vacuum filtration, and obtaining a chopped fiber mat preform; Step 4, soaking the chopped fiber mat prepared in step 3 in a 0.01 mol / L ferrous sulfate-polyvinyl alcohol solution, vacuum impregnating, and drying at 70° C. for 6-12 hours; Step 5, placing the sample prepared in step 4 into a chemical vapor deposition furnace, heating to 500°C under argon protection, with an argon flow rate of 1 L / min during the heating process; turning off the argon, introducing hydrogen and keeping warm for 1 hour, with a hydrogen flow rate of 200-250 mL / min, then turning off the hydrogen; introducing argon and heating to 1020°C, introducing natural gas, with a natural gas flow rate of 0.3 L / min, and keeping warm for 2 hours; Step 6, placing the sample prepared in step 5 into a chemical vapor infiltration furnace, heating to 1070°C under argon protection at 2.4 L / min, introducing natural gas at 0.8 L / min, and keeping the temperature for 1 h to prepare a porous hybrid network structure; Step 7, placing the porous hybrid network structure into a graphitization furnace and heat treating it at 2450° C. to obtain a porous hybrid carbon skeleton; Step 8, immersing the graphitized porous hybrid carbon skeleton in a polydimethylsiloxane solution with a mass ratio of resin to curing agent of 100:26.55, and vacuum immersing for 30 min; Step 9: Place the sample from step 8 in an oven, heat to 150°C, and cure for 120 min.

[0038] In this embodiment, the volume fraction of carbon fiber in the hybrid carbon skeleton is 4.8%, the volume fraction of carbon nanotubes is 0.5%, the volume fraction of pyrolytic carbon is 2.2%, the volume fraction of polydimethylsiloxane is 77.5%, and the thermal conductivity along the thickness direction of the composite material is 9.5 W / m·K.

[0039] Comparative Example Step 1, chop the mesophase pitch-based carbon fiber into 3-5 mm, take 0.15-0.3 g, and pre-oxidize in a muffle furnace at 390° C. for 90 min to remove the surface sizing agent; Step 2, placing the chopped fibers prepared in step 1 into a 20wt% sodium polyacrylate solution, and stirring by magnetic force to obtain a uniformly dispersed chopped fiber suspension; Step 3, pouring the chopped fiber suspension into a suction filtration device, performing vacuum filtration, and obtaining a chopped fiber mat preform; Step 4, placing the sample prepared in step 3 into a chemical vapor infiltration furnace, heating to 1070°C under argon protection at 2.4 L / min, introducing natural gas at 0.8 L / min, and keeping the temperature for 6 h to prepare a porous hybrid network structure; Step 5, placing the porous hybrid network structure into a graphitization furnace and heat treating it at 2450° C. to obtain a porous hybrid carbon skeleton; Step 6, immersing the graphitized porous hybrid carbon skeleton in a polydimethylsiloxane solution with a mass ratio of resin to curing agent of 100:26.5, and vacuum impregnating for 30 min; Step 7: Place the sample from step 6 in an oven, heat to 150°C, and cure for 120 min.

[0040] In this comparative example, the volume fraction of carbon fiber in the carbon skeleton is 4.2%, the volume fraction of pyrolytic carbon is 6.4%, the volume fraction of polydimethylsiloxane is 68.4%, and the thermal conductivity along the thickness direction of the composite material is 2.5 W / m·K.

[0041] Effect example like Figure 2 As shown in the figure, it is a schematic diagram of the carbon nanotube / pyrolytic carbon network structure constructed by the present invention. As can be seen from the left middle figure, the carbon nanotubes 2 grown in situ on the carbon fiber grow and extend radially from the radial direction of the carbon fiber 1, opening up the radial heat conduction channel of the carbon fiber 1. As can be seen from the right middle figure, after the chemical vapor infiltration of the pyrolytic carbon 3, the carbon nanotubes and the carbon fiber support each other, and the carbon nanotube / pyrolytic carbon network structure is constructed in the direction perpendicular to the carbon fiber, which reduces the contact thermal resistance of the hybrid carbon skeleton, forms a stable 3D high thermal conductivity network structure, and realizes the improvement of thermal conductivity in the direction between the fiber layers.

[0042] like Figure 3 As shown, it is the hybrid carbon skeleton microstructure of carbon nanotubes grown for 4 hours and pyrolytic carbon deposited for 6 hours in this embodiment 1. Carbon fibers 5, carbon nanotubes 4, and pyrolytic carbon are overlapped together to form a 3D network structure. It can be seen from the figure that the carbon nanotubes induced to grow in embodiment 1 of the present invention can reach a length of millimeter level.

[0043] like Figure 4As shown, it is a comparison of the thermal conductivity of the high thermal conductivity carbon skeleton / resin-based composite material prepared by the present invention. The thermal conductivity of the epoxy resin composite material in Example 1 is 20.9 W / m·K, wherein the volume fraction of the hybrid carbon skeleton is 19.2%; the thermal conductivity of the polydimethylsiloxane composite material in Example 2 is 18.8 W / m·K, wherein the volume fraction of the hybrid carbon skeleton is 17.2%; the thermal conductivity of the polydimethylsiloxane composite material in Example 3 is 9.5 W / m·K, wherein the volume fraction of the hybrid carbon skeleton is 7.5%; the thermal conductivity of the composite material in the comparative example is 2.5 W / m·K, wherein the volume fraction of the hybrid carbon skeleton is 10.6%.

[0044] The present invention and its implementation methods are described above, and such description is not restrictive, and the actual implementation methods are not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design structures and embodiments similar to the technical solution without creativity, which should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high thermal conductivity carbon skeleton resin-based composite material, characterized in that: The following steps are involved: The short-cut mesophase pitch-based carbon fibers are uniformly dispersed in a dispersant solution, vacuum-filtered, immersed in a mixed solution of a binder and a carbon nanotube growth catalyst, and dried to obtain a carbon fiber substrate material; Reducing the carbon fiber base material, inducing the growth of carbon nanotubes on the surface of the carbon fiber by chemical vapor deposition, and depositing pyrolytic carbon by chemical vapor infiltration to obtain a porous hybrid network structure, and graphitizing the porous hybrid network structure to obtain a porous hybrid carbon skeleton; The porous hybrid carbon skeleton is cured by using resin to obtain the high thermal conductivity carbon skeleton resin-based composite material.

2. The method for preparing the high thermal conductivity carbon skeleton resin-based composite material according to claim 1, characterized in that: The mass fraction of the dispersant in the dispersant solution is 0.1-5 wt %, and the dispersant is one or more of sodium polyacrylate, polyvinyl pyrrolidone, and acrylic acid.

3. The method for preparing the high thermal conductivity carbon skeleton resin-based composite material according to claim 1 or 2, characterized in that: The binder is one or more of polyvinyl alcohol, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, and polyethylene glycol; the carbon nanotube growth catalyst is one or more of ferrous sulfate, ferric nitrate, nickel nitrate, and cobalt nitrate; the mass fraction of the binder in the mixed solution is 1-20 wt%, and the mass fraction of the carbon nanotube growth catalyst is 0.5-2 wt%.

4. The method for preparing the high thermal conductivity carbon skeleton resin-based composite material according to claim 1, characterized in that: During chemical vapor deposition, an alkane precursor is introduced at 900-1100° C.; the alkane precursor is one or more of natural gas, methane, ethane, and propylene; and the flow rate of the alkane precursor is 0.05-0.5 L / min.

5. The method for preparing the high thermal conductivity carbon skeleton resin-based composite material according to claim 1, characterized in that: During chemical vapor infiltration, the temperature is raised to 800-1200°C and a pyrolytic carbon precursor is introduced; the pyrolytic carbon precursor is one or more of natural gas, methane, ethane, propylene, and ethanol; and the flow rate of the pyrolytic carbon precursor is 0.1-3 L / min.

6. The method for preparing the high thermal conductivity carbon skeleton resin-based composite material according to claim 1, claim 4 or claim 5, characterized in that: During the chemical vapor deposition process, the protective gas flow rate is 0.2~5 L / min, hydrogen is used as a reducing agent during the reduction process, and the hydrogen flow rate is 100~500 mL / min. During the carbon nanotube growth process, the protective gas flow rate is 0.5~5L / min; During the chemical vapor infiltration process, the protective gas flow rate during the heating process is 0.1~5 L / min, and the protective gas flow rate during the pyrolytic carbon deposition process is 0.2~5 L / min; The protective gas is argon or nitrogen.

7. The method for preparing a high thermal conductivity carbon skeleton resin-based composite material according to claim 1, characterized in that: The resin is one or more of polysiloxane, epoxy resin, phenolic resin, polyurethane and polyimide.

8. A high thermal conductivity carbon skeleton resin-based composite material prepared according to the preparation method of a high thermal conductivity carbon skeleton resin-based composite material according to any one of claims 1 to 7.

9. The high thermal conductivity carbon skeleton resin-based composite material according to claim 8, characterized in that: The adjacent carbon fibers are connected by carbon nanotubes coated with pyrolytic carbon or by pyrolytic carbon.

10. The high thermal conductivity carbon skeleton resin-based composite material according to claim 8 or claim 9, characterized in that: In the porous hybrid network structure, the volume fraction of the short-cut mesophase pitch-based carbon fibers is 4.0-10.0%, the volume fraction of the carbon nanotubes is 0.2-10.0%, and the volume fraction of the pyrolytic carbon is 1.0-20.0%.

Citation Information

Patent Citations

  • Preparation method of high thermal conductivity carbon / carbon composite material

    CN109437949A

  • Carbon nano tube deposited carbon-carbon composite material

    CN113636854A

  • Process and system for additive manufacturing of carbon scaffolds

    WO2023205309A1

Cited By

  • High-thermal-conductivity porous carbon framework material as well as preparation method and application thereof

    CN122167191A

  • Micro-nano hierarchical pore carbon skeleton material and preparation method thereof

    CN122301558A

  • High thermal conductivity and electromagnetic shielding composite material and preparation method thereof

    CN122751546A